Sunset at Zero Point - Stålenhag, Simon (Saga Press, 2025)
"Beginning in 2024, yet set largely during the early 2000s, Sunset at Zero Point unfolds on a secluded Swedish island, home to a secret weapon lab that has been off-limits for years, evoking the bestselling works of Jeff VanderMeer's Annihilation and Emily St. John Mandel's Station Eleven. Stêalenhag's masterful storytelling and hyper-realistic art transports you to an alternate history revealing his most intimate work to date, delving into themes of masculinity, friendship, and sexuality through the lens of a queer science fiction tale. The story spans decades following two young men, stuck in the past and each other's orbit, as fleeting moments become defining memories as they set out to explore the forbidden zone together. Set against the backdrop of Stålenhag's native Sweden and based on the alternate version of Mèalarèoarna outside of Stockholm, Sunset at Zero Point juxtaposes giant futuristic machines with the inner turmoil of its characters facing a social dystopia, crafting a narrative that isboth visually stunning and emotionally resonant."--